Dialectology as dialectic : interpreting Phula variation - Pelkey, Jamin R., 1974- (Trends in linguistics. Studies and monographs ;, 2011)
Undertaking a broadscale experiment in theory and praxis, this book demonstrates grounds for insisting on a more integrational approach to dialectology while simultaneously demonstrating grounds for defining the hidden Phula languages of the Sino-Vietnam borderlands. The modern languages and their ancestral lineage are defined dialectically, through dynamic syntheses of correlative perspectives.